How do world-class nordic combined athletes differ from specialized cross-country skiers and ski jumpers in sport-specific capacity and training characteristics? - Sandbakk, O.; Rasdal, V.; Bråten, S.; Moen, F.; Ettema, G. (International Journal of Sports Physiology and Performance, 2016)
Purpose: